Boosting Specific Energy and Power of Carbon-Ionic Liquid Supercapacitors by Engineering Carbon Pore Structures - Zhang, Dong; Gao, Hongquan; Hua, Guomin; Zhou, Haitao; Wu, Jianchun; Zhu, Bowei; Liu, Chao; Yang, Jianhong; Chen, De (Frontiers in Chemistry, 2020)
Carbon-Ionic Liquid (C-IL) supercapacitors is promising to provide high capacitance and high operating voltage, thus high specific energy. It is still highly demanding to enhance the capacitance in order to achieve high power and energy density. We synthesized a high pore volume and specific surface area activated carbon material with a slit mesoporous structure by two-step processes of carbonization and activation from polypyrrole. The novel slit pore structured carbon materials provide a specific capacity of 310 F g-1 at 0.5 A g-1 for C-IL supercapacitors, which is among one of the highest recorded specific capacitances. The slit mesoporous activated carbons have maximum ion volume utilization of 74%, which effectively enhance ion storage and a better interaction with ions in ionic liquid electrolyte, thus provide superior capacitance. We believe that this work provides a new strategy of engineering pore structure to enhance specific capacitance and rate performance of C-IL SCs.